Stress, Challenges and Expectations Efforts to Improve Nursing Students' Resilience During Clinical Practice Education - Ira Kusumawaty; Jawiah; Rehana; Yunike Yunike (Postgraduate, University of Mataram, 2023)
Nursing students often face problems in the form of stress and challenges when carrying out clinical nursing practice; it can worsen the quality of service in the clinic. Resilience is suspected to improve individuals in carrying out self-management well so that the process of adapting to problems can be carried out adaptively. It is essential to know the resilience of nursing students and the expected efforts so that they can overcome problems in the optimal service setting. This study explores stress, challenges, or efforts to increase resilience in nursing students in clinical practice education. According to the inclusion criteria, sixteen nursing students were involved in this qualitative study using this phenomenological approach. The process of data analysis using the Collaizi method was carried out, starting from reading the data repeatedly, forming categories to formulating themes. Triangulation efforts were carried out by involving three student supervising nurses to ensure the suitability of the information that had been obtained from student nurses. This study resulted in three themes: difficulties during clinical education challenges when carrying out clinical education and expectations for efforts to increase student resilience. It was concluded that there was a correlation between stress, challenge, and strength of nursing students and the interdependence between the three components. It is necessary to prepare nursing students' resilience before undergoing clinical practice by utilizing the potential supported by technological advances so that students can manage themselves well in dealing with various complicated problems in the clinical practice learning setting.